PENGARUH PENERAPAN e-SPT PPN TERHADAP EFISIENSI PENGISIAN SPT MENURUT PERSEPSI WAJIB PAJAK (Survey Terhadap PKP di KPP Pratama Semarang Candisari) - Afifatul Jannah, 10.05.52.0029; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of e-SPT PPN implementation to SPT charging efficiency as perception by the taxpayer.The population was registered corporate taxpayer in KPP Pratama Semarang Candisari. The sample in this study is based on probability sampling with simple random sampling as a technique of sampling. Data were collected by distributing questionnaires to a representative of corporate taxpayer who came to KPP Pratama Semarang Candisari for reporting SPT Masa PPN using e-SPT application.The method of analysis used in this study is a simple linear regression analysis. Based on the results of the analysis showed that the application of e-SPT PPN positive and significant impact on the efficiency of charging SPT.Keywords: e-SPT PPN, Charging Efficiency SPT